The science of literature : essays on an incalculable difference - Muller-Sievers, Helmut; Smith, Chadwick Truscott; Babinski, Paul; Wellbery, David E. (Berlin : De Gruyter, 2015)
Do literary texts provide distinctive access to the history of science? Is the study of literature based on scientific procedures? Is there a connection between scientific processes and literary forms? The essays in this collection show how literary and scientific texts from the late 18th to the late 19th centuries revolve around these questions. What emerges is a picture of the mutual dependence and the incalculable difference between literature and science in the period of their modern formation. --
Introduction: -- A science of literature? 1 -- 1) poetics of the life sciences 13 -- Formative forces: Biological, philosophical, and linguistic generativity 15 -- Divining relations: Forms of generational recognition around 1800 34 -- Tidings of the earth: towards a history of romantic Erdkunde 47 -- On nerve fibers: rhetoric and brain anatomy in Georg Bhner 69 -- 2) the science of reading 91 -- Reading off: On the emergence of the scientific gaze 93 -- On the margins of Derrida's terminology: Deconstruction, dissemination, mise en ab{u3A6D}e 107 -- What does it mean to orient oneself in thinking? 123 -- A tremendous chasm: Nietzsche, the birth of tragedy, and the measure of poetry 141 -- 3) the Applied science of literature 163 -- Torque: life and motion in the 19th century 165 -- A doctrine of transmissions: on the classification of machines around 1800 176 -- The novel machine: narration in the 19th century 195 -- The moment of narration: outlines for a kinematic study -- Of Goethe's Wilhelm Meisters Wanderjahre 209 -- Afterword by David E. Wellbery 227 -- List of first publications 239 -- Bibliography 241.
Includes bibliographical references (pages 241-256) and index.
Keywords: Literature and science -- History and criticism; German literature -- 18th century -- History and criticism; German literature -- 19th century -- History and criticism